CHARACTERISTICS OF RELICS AND ARTIFACTS AT STONE-TOOL-CRAFTING WORKSHOP RELICS IN THE PREHISTORIC PERIOD IN THE CENTRAL HIGHLANDS - Lê Xuân Hưng (Tạp chí Khoa học Đại học Đà Lạt)
This paper investigates the crafting activities of stone tool making, an essential manufacturing industry in prehistoric socio-economic structure in the Central Highlands from 4,000BP. Based on the data of 50 workshop relics of the post-Neolithic period discovered in Gialai, Daklak, Daknong, and Lamdong provinces, the article identifies the existence of four stone-tool-making centers. In each center, the quarrying process and the types of stones used for machining are different. This creates different types of products and the scope of using stone-tool models is, therefore, varied in the Central Highlands. The existence of these factory relics not only proves the post-Neolithic inhabitants in the Central Highlands were highly specialized but had a deep division of labor in production. The circulation of products created a relatively similar development throughout the Central Highlands, which is a critical premise for the emergence of the Metal Age in this region.